2015
DOI: 10.1097/aog.0000000000000634
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic Use of Negative Pressure Wound Therapy After Cesarean Delivery

Abstract: Our cost-benefit analysis provides economic evidence suggesting that negative pressure wound therapy should not be used on closed laparotomy incisions of patients with low risk of postcesarean delivery surgical site infections. However, among patients with a high risk of surgical site infections, prophylactic negative pressure wound therapy is potentially cost-beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Three studies on cost effectiveness in a gynecologic population have been performed. [ 44 46 ] Their results show a potential for pNPWT to be cost effective, especially in patient groups with high risk of SSI, such as clean-contaminated operations, or operations performed upon patients with intrinsic risk factors, such as obesity, diabetes, or immunosuppressive medication.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies on cost effectiveness in a gynecologic population have been performed. [ 44 46 ] Their results show a potential for pNPWT to be cost effective, especially in patient groups with high risk of SSI, such as clean-contaminated operations, or operations performed upon patients with intrinsic risk factors, such as obesity, diabetes, or immunosuppressive medication.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of prophylactic negative pressure wound therapy after CD in morbidly obese women, however, demonstrated fewer wound complications [61, 62]. A cost-benefit analysis showed that negative pressure wound therapy is only beneficial if the risk of surgical site infection is greater than 14% [63]. A large randomized controlled trials comparing prophylactic negative pressure wound therapy with standard dressing in women with obesity would be useful.…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…On the other hand, pNPWT also incurs additional costs. We identified three studies [2527] on cost-effectiveness of pNPWT and these were all performed in a gynaecological population. Lewis et al [26] found that the risk of wound complications must be reduced by 33% for pNPWT to achieve cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…For obese and morbid obese patients, required reduction was slightly less. Echebiri et al [25] concluded that if surgical site infection rates are greater than 14%, pNPWT could be cost-beneficial depending on the degree of reduction in surgical site infections. At a surgical site infection rate of 30%, the rate must be reduced by 15% for pNPWT to become the preferred strategy.…”
Section: Discussionmentioning
confidence: 99%